A survey of machine learning applications in digital forensics - Hilmand Khan; Sarmad Hanif; Bakht Muhammad (Trends in Computer Science and Information Technology - Peertechz Publications, 2021)
We address the role of machine learning in digital forensics in this paper, in order to have a better understanding of where machine learning stand in today's cyber security domain when it comes to collecting digital evidence. We started by talking about Digital Forensics and its past. Then, to illustrate the fields of digital forensics where machine learning methods have been used to date, we recommend a brief literature review. The aim of this paper is to promote machine learning applications in digital forensics. We went through different applications of machine learning in different areas and analysed how machine learning can potentially be used in other areas by considering its current applications and we believe that the ideas presented here will provide promising directions in the pursuit of more powerful and successful digital forensics tools.